NARASI HEROISME PEREMPUAN DALAM ISU LINGKUNGAN (Analisis Framing Berita Farwiza Farhan di Media Daring Lokal dan Nasional) - Fitri, Ainal; Maulina, Putri (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2020)
Environmental discourse is considered as one of the essential narratives since it involves the role of women. In the gender perspective, women in environmental issues are often described as a sidekick. Farwiza Farhan is one of the environmentalists who contributes to the environmental campaign effort. The study aims to focus on the framing of Farwiza Farhan’s figure against her contribution as the keeper of the Leuser Ecosystem (KEL) on online media environmental reports. This study used the Framing Analysis approach, Environmental Journalism, and Heroism concept. The researchers chose and analyzed three news from online news media: serambinews. com as a local source; and republika. co. id and bbc. com as national sources. This research was analyzed by using Zhongdang Pan and Gerald M. Kosicki’s Framing Analysis method. The finding shows that the news media frames Farwiza Farhan as an environmental activist with a heroism narrative. Farwiza is portrayed as a heroic, selfless, courageous, and intelligent personality. She is adaptive and determined to deal with conflict, and she also has initiative and leadership. Heroism is perceived as an environmental perspective-journalism strategy of online news media to deliver environmental knowledge and to raise public awareness towards the environmental issue.